Analisis Framing Berita Mengenai Childfree dalam Media Online Republika.co.id dan Kompas.com - Alfariz, Sandy Muhamad; Haloho, Heppy New Year (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
This study aims to look at the different frames of Republika.co.id and Kompas.com in covering issue of childfree. This research uses framing analysis method. The results of this study indicate that there are differences in the frames used by Republika.co.id and Kompas.com in covering the issue of childfree. In Republika.co.id's framework, childfree is considered as a problem that is contrary to the Islamic religion. In Kompas.com's frame, childfree is seen from broader perspective and does not see only one side.